Adobe® Flex® 3 : using Flex with data services : developing Flex applications with BlazeDS (Adobe Systems, 2008)
BlazeDS provides a set of services that lets you connect a client-side application to server-side data, and pass data among multiple clients connected to the server.BlazeDS implements real-time messaging between clients.